New essays in the legal and political theory of property/edited by Stephen R. Munzer - "Munzer, Stephen R. (ed.)" (Cambrige, 2001)
There has always been much controversy surrounding property rights in legal and political philosophy. Thinkers such as Plato, Locke, Kant, Hegel and Marx have all offered different views on the idea of property. This collection of essays, written by some of the most eminent scholars in the field, examines the most central issues of property theory from a variety of perspectives. The essays discuss whether property may be dissipated or used imprudently with impunity, and analyse how a person's property should be distributed after death. They survey the economic landscape of intellectual property and show that Locke's celebrated justification for private property falters when it comes to copyrights and patents. They also demonstrate how important it is that institutions of property be carefully justified. The variety and originality of these essays are evidence that the theory of property is one of the most exciting areas of intellectual inquiry in the humanities and social sciences.
Keywords: Property